2014
DOI: 10.1103/physreve.89.032805
|View full text |Cite
|
Sign up to set email alerts
|

Capital death in the world market

Abstract: We study the gross domestic product (GDP) per capita together with the market capitalization (MCAP) per capita as two indicators of the effect of globalization. We find that g, the GDP per capita, as a function of m, the MCAP per capita, follows a power law with average exponent close to 1/3. In addition, the Zipf ranking approach confirms that the m for countries with initially lower values of m tends to grow more rapidly than for countries with initially larger values of m. If the trends over the past 20 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For further research, the East Asian stock markets can be further explored on the lines of recent work of Avakian et al [84]. On a slightly different tangent, they provide interesting findings for the effect of globalization on the stock markets.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 96%
“…For further research, the East Asian stock markets can be further explored on the lines of recent work of Avakian et al [84]. On a slightly different tangent, they provide interesting findings for the effect of globalization on the stock markets.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 96%
“…Next, due to lack of data for physical capital, we take market capitalization as a proxy for physical capital31, as more data is available. Avakian et al 31.…”
Section: Resultsmentioning
confidence: 99%
“…Avakian et al 31. analyzed over the 17-year period 1994–2010 the set of 68 countries for which there are published values of both GDP and MCAP, and reported that the GDP per capita , and the MCAP per capita , follow a power law with average exponent close to 1/3.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, a lot of physicists devoted to the study of financial dynamics in the past two decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and some stylized facts have been revealed from the statistical physics perspective. Scaling behavior of the return and return interval distributions has been observed for different markets [1][2][3][4][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%